SOSIALISASI DAN PEMAHAMAN PRINSIP-PRINSIP HUKUM EKONOMI ISLAM DI SMK MUHAMMADIYAH 2 KLATEN UTARA SEBAGAI REFERENSI PENGELOLAAN KEUANGAN SYARIAH - Sulistyaningsih, Nur (Fakultas Hukum Universitas Semarang, 2023)
Indonesia has experienced an economic crisis that has an impact on the disruption of financial system stability. As a nation where the majority of the population embraces Islam, some people use Islamic economics as an alternative. This is evidenced by the rise of Baitul Maal wa Tamwil (BMT) in the midst of society. In addition, many financial institutions have a sharia concept.However, there are still many who are not familiar with the principles of Islamic economic law. So that the introduction and understanding should be presented since school. SMK 2 Muhammadiyah North Klaten is an Islamic-based vocational school in the Klaten area. One of the competencies and skills taught at the school is accounting and financial management. The facility also has a mini bank which is a place for students to carry out economic activities.The program targets through socialization with the theme of the basic principles of Islamic economic law aimed at students of SMK Muhammadiyah 2 Klaten Utara who are the nation's assets. The method of implementing this program is through socialization and assistance which contains exposure to legal arrangements relating to Islamic economics and sharia business.The expected results of this program are 1) students are able to understand the basic principles of Islamic economic law in financial management 2) students are able to apply and apply these principles in financial management.